The COVID-19 pandemic and self-reported food insecurity among women in Burkina Faso: evidence from the performance monitoring for action (PMA) COVID-19 survey data - Ortis Yankey; Marcellinus Essah; Prince M. Amegbor (BMC Women's Health)
Abstract Background The COVID-19 pandemic led to widespread economic disruptions, with government-imposed restrictions and lockdowns significantly affecting livelihoods globally. Burkina Faso, a country with pre-existing vulnerabilities in food security, experienced considerable challenges during this period. The aim of this study was to examine how COVID-19-related income losses is associated with self-reported food insecurity among women in Burkina Faso in 2020. The study also examined whether there was an increase in self-reported food insecurity among women during the COVID-19 restrictions compared with the pre-pandemic era. Methods We conducted a cross-sectional analysis using data from the Performance Monitoring for Action (PMA) female survey, which included 3,499 women from Burkina Faso. This study examined the associations between socioeconomic variables, such as age, education, household income loss, and food insecurity. We conducted two analyses using logistic regression. The first analysis focused on self-reported food insecurity and its association with the socioeconomic variables, and the second analysis focused on whether there was an increase in self-reported food insecurity compared with pre-pandemic levels and its association with the socioeconomic factors. We controlled for relevant confounders in the analysis and presented the results as adjusted odds ratios (AORs) with 95% confidence intervals (CIs). Results Our findings indicated that 16.97% of women reported experiencing food insecurity during the pandemic period. Compared with women with no income loss, women who experienced partial household income loss were 1.82 times (95% CI: 0.98–3.38) more likely to report food insecurity, whereas those who experienced complete income loss were 5.16 times (95% CI: 2.28–9.43) more likely to report food insecurity. The study, however, did not find a statistically significant increase in self-reported food insecurity due to COVID-19 restrictions compared with pre-pandemic levels. Conclusions This study demonstrated that income loss due to COVID-19 restrictions profoundly affected women’s food security in Burkina Faso. The significant associations between income loss and increased food insecurity underscore the need for targeted interventions and safety nets to support women during public health crises.